Impacts of Management Education on Entrepreneurial Intent in Birendranagar Municipality, Surkhet - Timilsena, Chhetra Mani (Journal of Entrepreneurship & Management Studies, 2025)
This study investigates the impact of management education on the entrepreneurial intentions of graduates in Birendranagar Municipality, Surkhet. Using a mixed-method approach, data were collected from 30 business firms, equally divided between those led by management graduates and non-management graduates. The study aimed to compare entrepreneurial traits and performance outcomes across these two groups. The results showed that management education positively impacts entrepreneurial intent, with management graduates exhibiting higher self-efficacy, risk-taking ability, and creative thinking. However, non-management graduates demonstrated higher levels of motivation and passion. The study concludes that while management education enhances certain entrepreneurial skills, intrinsic motivation remains crucial to entrepreneurial success.